Development of molybdenum-induced osteodystrophy fibrosa in goats - Mirwan, Nabil Milad Althabet (2013)
Most researches on molybdenosis are correlated to non-skeletal signs of copper (Cu) deficiency irrespective of the inducing agent. However, the detailed role of excess molybdenum (Mo) intake on skeletal effect leading to osteodystrophy fibrosa (ODF) in goats was never documented. It is hypothesized that through a proper experimental regime, excess Mo in the presence of sulphur (S) will induce corporeal skeletal changes in goats. The aim of this study was to evaluate the ability and effectiveness of high Mo with or without Cu and/or S to induce skeletal changes (ODF) and oxidative stress in goats. The parameters measured to verify the aim includes assessing potential clinicopathological hallmark of Mo excess, the concentration of selected minerals in bone and relevant tissues during the development of ODF, determination of the predominant biomarkers of bone metabolism turnover of ODF, and finally to investigate whether Mo with or without Cu and S can induce oxidative stress in goats. A total of 26 Boer bucks with average body weight of 20 kg, aged between 9-10 monthsold were divided into eight groups. Three bucks each were allocated to six groups viz;unsupplemented (Control) while others were supplemented with the following: molybdenum (Mo), copper (Cu) and sulphur (S), copper plus S (Cu+S) and Mo plus Cu (Mo+Cu). The other two groups that were comprised of four bucks each were the Mo plus S (Mo+S) and Mo plus Cu plus S (Mo+Cu+S). The study was conducted for 13 weeks. Three groups (Mo, Mo+S and Mo+S+Cu) receiving an oral supplementation of 2g Mo/goat developed clinical signs of molybdenosis and/or Cu deficiency rather than an overt ODF. However, apart from low calcium and high bone alkaline phosphatase (BALP), ODF was successfully induced in Mo group and Mo+S group and to lesser extent in the Mo+S+Cu group. Pathologically, ODF was confirmed by marked fibrous deposition and osteoclasia in bone and the mandible was most susceptible affected bone in goats. In addition to ODF lesions, a variety histopathological change related to molybdenosis and/or Cu deficiency were also observed in these three groups. No significant lesions were observed in other treatment groups. The concentration of Mo in plasma of goats during experimentation were obviously significantly higher in Mo group than other groups which peaked at Weeks 8 and 13, except that terminal values of Mo level in Mo+S group and Mo+ Cu+S groups. In these two latter groups, the end point concentrations were higher than initial ones. The lowest values of plasma copper levels were obtained in Mo+S group and Mo+Cu+S group at Weeks 8 and 10 and in the Mo group at Week 13. On the other hand, S concentrations were slightly different between treated groups until the end experiment. The concentrations of Mo in the liver were significantly highest within the groups supplemented with Mo and conformed to those clinical molybdenosis rather than ODF. There was a much higher concentration of Mo in the mandible than the femur and both being highest in the Mo group and Mo+S groups, respectively. Hepatic Cu concentration was significantly different between all groups, with the highest occurring in the Cu group and the lowest in Mo+Cu group. The lowest mandibular Cu concentration was in Mo+ Cu+S and the highest was in Cu+S group. Significantly higher hepatic S concentration was found within groups supplemented with S especially in the Cu+S group. Furthermore, the lowest concentration of mandibular S and femoral S were seen in Mo+Cu group and control group respectively, while the highest was observed in S group of both bones. The BALP and C-telopeptide (CTX-I) biomarkers fluctuate in Mo group from Week 6 until the end of the experiment. The concentration of CTX-I was significantly lowest in the Mo group, while it decreased at Weeks 8 and 10 in Mo+S group and at Week 6 onwards in Mo+Cu+S group. The concentration of parathyroid hormone (PTH) remained high in the Mo, Mo+S and Mo+Cu+S groups. Apart from a decrement in the Mo+Cu group and no significant difference in both control and Cu+S group, the concentration of plasma malondialdehyde (Pl-MDA) as an oxidative stress biomarker was significantly increased in Mo, Cu, S, Mo+S and Mo+Cu+S groups until the end of the experiment. The concentration of erythrocyte super oxide dismutase and glutathione peroxidase as antioxidative markers yielded significant difference in all treated groups and being the lowest in Mo, Mo+S and Mo+Cu+S groups during this study. In conclusion, it was found that excess Mo intakes especially in the presence of S may lead to the progression of the development of Mo-induced ODF due to Cu deficiency.